The cutting edge [videorecording (DVD)] - Glaser, Paul Michael; Sweeney, D. B. (Daniel Bernard), 1961-; Kelly, Moira; Dotrice, Roy, 1923-2017; O'Quinn, Terry, 1952- (MGM Home Entertainment ; [Sony Pictures Home Entertainment, distributor], 2006)
Romantic comedy about a handsome, self-centered ex-ice hockey player and a figure skater with a prima donna attitude who dislike each other intensely, but they team up because to each other they represent a last resort for their prospective careers in the rink.